2013
DOI: 10.1097/ijg.0b013e31824caf90
|View full text |Cite
|
Sign up to set email alerts
|

Idebenone Prevents Human Optic Nerve Head Astrocytes From Oxidative Stress, Apoptosis, and Senescence by Stabilizing BAX/Bcl-2 Ratio

Abstract: Purpose: Oxidative stress plays an important role in the pathogenesis of several neurodegenerative diseases including glaucoma. Astrocytes are supposed to play a role in glaucoma pathogenesis. This study investigates the antiapoptotic and cytoprotective effects of idebenone on optic nerve head astrocytes (ONHA) under oxidative stress.Methods: ONHA were treated with 1 to 150 mM idebenone. Cell viability (MTT assay and live-dead assay), induction of intracellular reactive oxygen species, senescence-associated b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 52 publications
(99 reference statements)
1
23
0
Order By: Relevance
“…Whereas astrocytes have the capacity to combat oxidative stress to the benefit of other adjacent cells, they themselves are still vulnerable to the actions of ROS, which can cause mitochondrial damage, accelerated senescence, and cell death [28,29]. Our results support these conclusions by demonstrating that at the site of lesion, astrocytes are the dominant cell type showing increased protein carbonylation post-CCI.…”
Section: Discussionsupporting
confidence: 88%
“…Whereas astrocytes have the capacity to combat oxidative stress to the benefit of other adjacent cells, they themselves are still vulnerable to the actions of ROS, which can cause mitochondrial damage, accelerated senescence, and cell death [28,29]. Our results support these conclusions by demonstrating that at the site of lesion, astrocytes are the dominant cell type showing increased protein carbonylation post-CCI.…”
Section: Discussionsupporting
confidence: 88%
“…fibroblasts and keratinocytes [25,44]. Also, in the eye, SA-β-Gal is elevated in senescent cells [19]. So, the results of this study underline the pivotal role of oxidative stress in aging and apoptosis of RPE cells.…”
Section: Discussionmentioning
confidence: 70%
“…A previous study showed stronger effects with pre- than with posttreatment [18]. Also, we [19] and others [20,21,22] showed promising results with pretreatment; therefore, we chose this regimen again for the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations